Measuring Performance for Sustainable Governance in Local Public Institutions - GÂF-DEAC, Ioan I.; PURCĂREA, Liviu; RĂDULESCU, Carmen-Valentina; TROACĂ, Victor Adrian (European Journal of Sustainable Development, 2025)
The intention of this text is to spotlight a few elements concerning the primary functions of organizational overall performance assessment structures (PMS) inside neighborhood public government in Romania (mayoralties) and the existing exploratory imaginative and prescient on those structures. According to a sociological survey carried out in 6 neighborhood organizations (municipalities) in North-West Romania (North-West Development Region of Romania), the consequences of the item suggest a low use of PMS in those institutions, which displays a restricted hobby from the primary actors. The consequences of the have a look at emphasize that overall performance assessment structures aren't but perceived as a powerful managerial device in neighborhood public administrations in Romania, no matter the reality that overall performance size is a substantial possibility for aid allocation, price range improvement or worker motivation. In this context, PMSs are used solely through human beings in control positions withinside the mayoralty, and the motive in their use is restricted to growing the decision-making process, statistical reporting or growing the exceptional of the offerings provided. Keywords: development, performance, public institution, system